2013
DOI: 10.22458/urj.v5i1.189
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of Helminth parasites in the gastro-intestinal tract of wild African sharptooth catfish Clarias gariepinus (Siluriformes: Clariidae) in Gwagwalada, Nigeria

Abstract: A study on the gastro-intestinal helminth parasites of wild C. gariepinus was carried out in Gwagwalada Area Council of FCT, Abuja, Nigeria. A total of 110 samples were examined which includes 42 males and 68 females. Forty-eight (43,64%) fishes were infected with various species of helminth, which includes Wenyonia spp (28,18%), Procamallanus laevionchus (11,82%) and Euclinostomum heterostomum (3,64%). The female fish had the highest percentage prevalence (28,18%) while the males had 15,46% prevalence. Most o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
3
3
1
Order By: Relevance
“…The results revealed that no significant differences were detected between prevalence of anisakid larvae infection and body length of fishes. This finding agreed with Olurin et al (2012) but disagreed with others (Khanum et al, 2011;Dan-Kishiya et al, 2012;Yakhchali et al, 2012;Esiest, 2013;Idris et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…The results revealed that no significant differences were detected between prevalence of anisakid larvae infection and body length of fishes. This finding agreed with Olurin et al (2012) but disagreed with others (Khanum et al, 2011;Dan-Kishiya et al, 2012;Yakhchali et al, 2012;Esiest, 2013;Idris et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…Current observation is consistent with the reports of Anosike et al (1992) and Omeji (2013) who observed more parasite infestation in male fish than the female. The observation is however at variance with that of (Emere and Egbe, 2006) and Dankishiya et al (2013) who reported higher intensity of helminth parasites in the gastrointestinal tract of female wild African sharp tooth catfish (Clarias gariepinus) in Gwagwalada of Federal Capital Territory, Nigeria than the male counterparts.…”
Section: Discussioncontrasting
confidence: 79%
“…We found that the prevalence of infection was unrelated to the fish's body length. This outcome was in agreement with the results of some previous studies(Kassem & Bowashi, 2015;Olurin et al, 2012) and disagreed with the results of other studies(Dan-kishiya et al, 2013;Esiest, 2013;…”
supporting
confidence: 80%